2013
DOI: 10.1080/10590501.2013.763577
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemoprevention by Polyphenols and Their Potential Application as Nanomedicine

Abstract: Today cancer is a leading cause of death among the developed countries. Its highly complex nature makes it difficult to understand as it entails multiple cellular physiological systems such as cell signaling and apoptosis. The biggest challenges faced by cancer chemoprevention/chemotherapy is maintaining drug circulation and avoiding multidrug resistance. Overall there is modest evidence regarding the protective effects of nutrients from supplements against a number of cancers. Numerous scientific literatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 186 publications
3
50
0
1
Order By: Relevance
“…Additionally, the mean BMI of breast cancer patients was 25.0 kg/m 2 , which was equal to the level of obese people. These results were consistent with other studies .…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, the mean BMI of breast cancer patients was 25.0 kg/m 2 , which was equal to the level of obese people. These results were consistent with other studies .…”
Section: Discussionsupporting
confidence: 94%
“…Table I shows that the preliminary phytochemical analysis of H-PIRE revealed a high content of phenols, flavonoids and proanthocyanidins, which are biologically active phytochemical compounds found in many medicinal herbal extracts. Secondary metabolites such as polyphenols and flavonoids interact with proteins and are useful for inhibiting multidrug resistance (25), suppressing tumor angiogenesis and preventing inflammation (26). Thus, the phytochemical composition of H-PIRE was consistent with the reported medicinal properties of P. indica.…”
Section: Resultssupporting
confidence: 67%
“…Encapsulating polyphenols in nanoparticles could enhance their biodistribution, solubility, and stability in the human body, while reducing their intense metabolism. Moreover, conjugating nanoparticles containing a specific polyphenol with an appropriate anticancer drug may improve internalization of these natural compounds into cancer cells, leading to improved anticancer activity [164]. Several studies have reported that nanotechnology enhanced ability of CUR to counteract the growth of various tumors.…”
Section: Nanotechnology and Polyphenolsmentioning
confidence: 99%
“…In this regard, several preclinical studies reported that the encapsulation of polyphenols in small nanoparticles enhanced their bioavailability and antitumor activity [152,153,154,155,156,164]. …”
Section: Perspective and Conclusionmentioning
confidence: 99%